Dietary Addition of Tributyrin Improved the Production Performance, Antioxidant Ability and Intestinal Health in Weaned Rabbits - Nanbin Zhang; Xianghui Li; Huijie Xu; Fuchang Li; Lei Liu (Animals, 2025)
The present study was conducted to investigate the effects of dietary addition of tributyrin on growth performance, antioxidant and intestinal health in weaned rabbits. Weaned Hyla rabbits (35 d, n = 1280) of similar body weight were randomly divided into four groups (eight replicates per group, 40 rabbits per replicate), fed diets with 0, 0.1%, 0.2% or 0.4% tributyrin addition. A 3-day pre-experimental period was followed by a 36-day trial period. Our results show that dietary addition of 0.2% tributyrin significantly increased the average daily gain (ADG) and final body weight (FBW) of rabbits, and decreased the diarrhea rate (p < 0.05). Dietary addition of 0.1% and 0.2% tributyrin significantly increased the average carcass weight and liver weight (p < 0.05). In the liver, dietary addition of tributyrin increased the content of glutathione peroxidase (GSH-PX) and total superoxide dismutase (T-SOD) compared with the control group (p < 0.05). Dietary addition of 0.1% and 0.2% tributyrin significantly increased the serum GSH-PX level (p < 0.05). Dietary addition of 0.2% tributyrin significantly increased the serum T-SOD level (p < 0.05). Dietary addition of 0.2% tributyrin significantly increased villus height/crypt depth (V/C) in the duodenum (p < 0.05). Dietary addition of 0.1–0.4% tributyrin significantly increased V/C in the jejunum (p < 0.05). Dietary addition of 0.1–0.2% tributyrin significantly increased the V/C in the ileum, but significantly decreased the content of serum diamine oxidase (DAO) and of D-lactic acid in serum (p < 0.05). In conclusion, dietary addition of tributyrin can improve the production performance and antioxidant ability of liver and serum, and improve the intestinal health by decreasing the diarrhea rate and the intestinal permeability and improving intestinal morphology in weaned rabbits. Based on the present results, the optimal level of tributyrin is 0.2% in the weaned rabbit diet.